Development Of Game Model Number Five Event In Sepak Takraw Branch In Central Java Players - et. al., Tri Aji, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to develop a new product for the Panca event game at the student level sepaktakraw branch, and test the effectiveness of the new product for the Panca event game at the student level sepaktakraw branch. This research method uses a research and development (R & D) model approach. The research design uses the Borg & Gall development model approach. With ten steps: Research and information collecting, the results of the needs analysis show the need for an effective, innovative game update that can be played by all players. 2) Planning, making a research plan by forming a team according to the expertise needed to assist the process of developing research products. 3) Develop a preliminary form of product, create a design model for the five-event game regulation guidelines accompanied by pictures in the form of a guide text book. 4) Preliminary field testing, testing early stage products involving 20 players as test subjects. 5) Main product revision, improving the developed product that has been tested. 6) Main field testing, re-testing the product with a larger number of players with 12 groups or 60 players. 7) Operational product revision, improving the product developed based on suggestions and input on field trials. 8) Operational field testing, the effectiveness test involves 80 players by comparing the previous numbers, quadrant, squad, double and five events, each number has four groups. 9) Final product revision, perfecting the five event products before they are disseminated. 10) Dissemination and implementation, this research has been socialized in FGD with the Central Java provincial government and in seminars or through international journals. The data analysis technique in this study used multivariate ANOVA (MANOVA) analysis. The results of this study are in the form of a product of the development of the five event game. This Panca Sepaktakraw event deserves to be a Sepaktakraw match number because the test results have proven to be effective..